2018
DOI: 10.1002/jmri.26301
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis of Multiparametric MRI Evaluates the Pathological Features of Cervical Squamous Cell Carcinoma

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
(36 reference statements)
6
34
2
Order By: Relevance
“…29 To date, it has already been shown that some MR parameters, including the tumor volume and the maximum diameter of the resectable CC on MRI, minimal ADC value, minimal ADC ratio, and the DCE parameters (K trans , V e ), may be used to predict LVSI. 2,30,31 In one study, the best distinguishing parameter was the minimal ADC ratio, with an AUC of 0.970; others ranged from 0.748 to 0.885. 2,30,31 In our study we found that the T 2 values could distinguish LVSI-positive and LVSI-negative CC, while the ADC values between the two groups did not show significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 To date, it has already been shown that some MR parameters, including the tumor volume and the maximum diameter of the resectable CC on MRI, minimal ADC value, minimal ADC ratio, and the DCE parameters (K trans , V e ), may be used to predict LVSI. 2,30,31 In one study, the best distinguishing parameter was the minimal ADC ratio, with an AUC of 0.970; others ranged from 0.748 to 0.885. 2,30,31 In our study we found that the T 2 values could distinguish LVSI-positive and LVSI-negative CC, while the ADC values between the two groups did not show significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…2,30,31 In one study, the best distinguishing parameter was the minimal ADC ratio, with an AUC of 0.970; others ranged from 0.748 to 0.885. 2,30,31 In our study we found that the T 2 values could distinguish LVSI-positive and LVSI-negative CC, while the ADC values between the two groups did not show significant differences. This may be due to tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2 weighted imaging (T2WI) is a stable and essential sequence of cervical scanning according to the protocol for staging and evaluation of cervical cancer proposed by the European Society of Urogenital Radiology 2010 17 . Although radiomics analysis of cervical tissue has been widely performed on T2W images 6,[18][19][20] , its nonquantitative nature underlines the need for investigating the reproducibility of this sequence in a multi-center scenario. Thus, the purpose of the current study was to quantitatively identify the influence of different scanners and acquisition parameters on the robustness of T2WI radiomics features (RFs) based on females' cervix, which might have some implications for further radiomics studies on cervical lesions.…”
mentioning
confidence: 99%
“…Previous studies have reported that tumor characteristics at the cellular and genetic levels can be re ected in the phenotypic patterns and subsequently captured by radiomics signatures [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%